Bulk Tank Somatic Cell Count and Associated Microbial Quality of Milk from selected Dairy Cattle Herds in Oyo State, Nigeria. (2018)
Improvement of traditional and nomadic milk production through dairy development program in Nigeria requires routine quality and safety monitoring of milk both at herd level and milk collection centers. A total of 411 bulk raw milk sam- ples aseptically obtained from Ibarapa, Oyo and Oke-Ogun industriai milk collection centers were subjected to California Mastitis Test (CMT), Bulk Somatic Celi Count (BSCC) and bacteriological analysis for assessment of quality and safety of milk from thè herds. One hundred and seven (26.0%) of thè samples were CMT positive, while 74.0% were negative to CMT. The overall mean BSCC, TAC and TCC were 1.27xl03± cells/mL, 1.12xl03± 34 cfu/mL, 97.8±9.8 cfu/mL in thè CMT negative milk samples while for thè strong positive samples thè mean BSCC, TAC and TCC were 4.33xl06 ± cells/mL, 2.35x10" ± 453 cfu/mL, 189.3±41.1 cfu/mL respectively; these were higher than thè Pasteurized Milk Ordinance acceptable limits. Positive corre- lation was found between CMT scores and bacterial contamination and between CMT scores and SCC was recorded. About 26.0% of thè samples with positive CMT could he considered unsafe due to strong correlation with microbial contamination that could result in milk bome zoonoses and public health hazards. However, a greater propor- tion (76.9%) of thè milk with negative CMT scores could be safe for human consump- tion after post-harvest pasteurization. Consequently, there is need to improve han- dling, environmental and milking hygiene; as well as proper herd and udder health management to improve quality and safety of Nigeria dairy products